CLOUD INFRASTRUCTURE EVOLUTION: FROM FOUNDATION TO IMPLEMENTATION - A COMPREHENSIVE ANALYSIS OF MODERN CLOUD ARCHITECTURE - Amit Sant (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive technical article explores the evolution and fundamental aspects of cloud infrastructure in modern software systems. The article examines the core building blocks, including virtualization, containerization, and Infrastructure as Code (IaC), while analyzing their impact on organizational efficiency and scalability. The article delves into hybrid and multi-cloud strategies, presenting real-world implementation examples from major providers like AWS and GCP. It further investigates best practices for high availability design, performance optimization, and security considerations in cloud environments. Through detailed analysis of market trends, adoption patterns, and technological advancements, the article provides insights into how organizations can effectively leverage cloud infrastructure while addressing challenges in cost management, security, and operational efficiency.